(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2017)
Many patients with chronic kidney disease eventually become anaemic. Generally, haemodialysis patients tend to have more severe anaemia than those receiving peritoneal dialysis, probably because of greater blood loss and haemolysis in haemodialysis patients and better removal of uncharacterized ‘middle molecules’ inhibitory to erythropoiesis in peritoneal dialysis patients. Haemodialysis generally improves the fluid environment of the erythrocytes by partial correction of the electrolyte disequilibrium, the acid-base status and the removal of a number of uremic substances that may possibly disturb both the biochemical and physical properties of the cells. However, transit of the cells through the extracorporeal circuit may have some detrimental effects on the cells, including exposure to a rapidly changing plasma osmolality, mechanical damage as a result of blood pump occlusion, bio-incompatibility of dialyser membranes and blood lines, as well as friction due to haemodialyser design. Effects of the extracorporeal circuit include direct haemolysis as well as morphological changes that could lead to in vivo post-dialysis haemolysis. This study is aimed at to compare the consequent changes in some of the haematological parameters related to RBC, viz. Hb and total count of RBC and PCV in patients receiving Maintenance haemodialysis (MHD) in their pre and post-dialysis blood samples and to show that there is no detrimental effects of haemodialysis procedure on these haematological parameters. It is a Hospital based, cross-sectional comparative study. The study population consisted of 40 patients of diagnosed case of chronic kidney disease patients on haemodialysis in the Department of Nephrology, Chittagong Medical College Hospital, Chittagong. The haematological changes before and after the ending of haemodialysis procedure were studied by complete blood count study by automated analyzer. Data were analyzed by statistical methods (Paired sample t-test). In our study the pre-dialysis and post-dialysis sample showed the mean(±SD) haemoglobin level was 7.76(±1.65) gm/dl and 8.34(±2.00) gm/dl respectively. Also this study shows highly significant difference between mean of pre-dialysis and post-dialysis haemoglobin level (p=0.004). In this study the pre-dialysis and post-dialysis sample showed the mean(±SD) RBC count was 2.71(±0.68) million/μl and 2.93(±0.78) million/μl respectively. This shows highly significant difference between mean of pre-dialysis and post-dialysis RBC count (p=0.000). This study also shows the Haematocrit / PCV (%) in pre-dialysis and post-dialysis sample of the patients. In pre-dialysis and postdialysis sample the mean(±SD) Haematocrit / PCV(%) was 26.46 (±7.34)% and 27.39 (±8.07)% respectively. This shows no significant difference between mean of pre-dialysis and post-dialysis Haematocrit / PCV(%) level (p=0.157). The results of this study revealed that significant changes in haematological parameters, specially, regarding Hb level, total count of RBC and no significant changes in PCV occur in patients receiving MHD during HD process in their postdialysis blood samples. And all these findings are consistent with each other. Study shows that there is no detrimental effects of haemodialysis procedure on these haematological parameters. JCMCTA 2016 ; 27 (2) : 72 - 76